Decision Support System in Determining Scholarship Recipient Lecturers Using the Simple Additive Weighting (SAW) Method - Pangaribuan, Nissi (Jurnal Matematika Dan Ilmu Pengetahuan Alam LLDikti Wilayah 1 (JUMPA), 2021)
The role of lecturers in higher education is one of the most influential parts of the quality of students produced. The educational qualification of lecturers is an important aspect of academic and institutional quality. So that many universities or educational institutions provide doctoral scholarship programs for potential lecturers.One of them is the Catholic University of Santo Thomas, Medan, which provides scholarships, namely doctoral scholarships for 5 outstanding lecturers. This research is a decision support system for doctoral scholarship recipients at the Catholic University of Santo Thomas Medan using the Simple Additive Weigting (SAW) method. The SAW method is used to determine the recipient of the S3 scholarship which is determined based on the criteria. This decision support system is built with a web-based application system as a tool in determining the decisions of lecturers who receive doctoral scholarships at the Catholic University of Santo Thomas Medan and uses MYSQL as a database.